THE STUDENTS’ DIFFICULTIES IN USING SIMPLE PRESENT TENSE: A CASE STUDY AT SENIOR HIGH SCHOOL STUDENT SIMPLE PRESENT TENSE - Rusdin Rusdin (Journal of English Language Teaching and Literature (JELTL), 2022)
This study aims to determine the problems faced by second-grade students in using the simple present tense at (Madrasah Aliyah Negeri) MAN Dompu. The data collection used in this research is interviews and tests, in order to find and classify the problems faced by second-grade students who have difficulty using the simple present tense. The research method used in this research is descriptive qualitative and quantitative methods. The population used in this study consisted of 5 classes and the sample was taken randomly, eight students in each class were used as samples. The number of samples is 40 students. The results of data analysis obtained through object tests and essay tests show that students' scores are very poor. This is evidenced by the average value of students is 3.9. Based on the test results, it shows that students have low ability in using the simple present tense, the students are quite interested in English subjects; English is very difficult for them; English teachers never give advice and motivation to students; the teacher never informs the students about the importance of learning English, especially the simple present tense; students have low motivation in learning English; English teachers never pay attention to students who have difficulty learning English; lack of stimulation for students in learning English; and students have low abilities. The researcher hopes that this research can contribute to teachers and students in the teaching and learning process of English, especially in the use of the simple present tense.